Determinants of infant feeding practices among Black mothers living with HIV: a multinomial logistic regression analysis - Josephine Etowa; Jean Hannan; Egbe B. Etowa; Seye Babatunde; J. Craig Phillips (BMC, 2021)
Abstract Background Infant feeding practices are imperative for babies' and mothers' health and emotional wellbeing. Although infant feeding may seem simple, the decisions surrounding it are complex and have far-reaching implications for women globally. This is an especially difficult concern among mothers living with HIV because breastfeeding can transmit HIV from mother to child. This is further complicated by cultural expectations in case of Black mothers living with HIV. This paper discusses determinants of infant feeding practices among Black mothers living with HIV who were on anti-retroviral therapy (ART) in two North American cites and one African city. Methods A cross-sectional, multi-country survey using venue-based convenience sampling of Black mothers living with HIV was employed. The effective response rates were 89% (n = 89) in Ottawa, Canada; 67% (n = 201) in Miami, Florida, US; and 100% (n = 400) in Port Harcourt, Nigeria, equaling a total sample size of 690. Data were collected in Qualtrics and managed in Excel and SPSS. Multinomial logistic regression analyses were used to determine the factors influencing the mothers' infant feeding practices (Exclusive Formula Feeding [EFF] = 1; Mixed Feeding [MF] = 2; and Exclusive Breastfeeding [EBF while on ART] =3). Results The results highlight socio-demographics, EFF determinants, and EBF determinants. The statistically significant determinants of infant feeding practices included national guideline on infant feeding, cultural beliefs and practices, healthcare systems, healthcare personnel, infant feeding attitudes, social support, and perceived stress. Mothers' mean ages were Ottawa (36.6 ± 6.4), Miami (32.4 ± 5.8), and Port Harcourt (34.7 ± 5.7). All sampled women gave birth to least one infant after their HIV diagnoses. Statistically significant (p < .05) determinants of EFF relative to MF were the national guideline of EFF (relative risk [RR] = 218.19), cultural beliefs (RR = .15), received healthcare (RR = 21.17), received healthcare through a nurse/midwife (RR = 3.1), and perceived stress (RR = .9). Statistically significant determinants of EBF relative to MF were received healthcare (RR = 20.26), received healthcare through a nurse/midwife (RR = 2.31), functional social support (RR = 1.07), and perceived stress (RR = .9). Conclusion While cultural beliefs and perceived stress favoured MF over EFF, advice of healthcare workers, and the care received from a nurse/midwife improved EFF over MF. Also while the mothers' perceived stress favoured MF over EBF, advice of their nurses or midwife and the social support improved EBF over MF. The providers advice was congruent with WHO and national guidelines for infant feeding among mothers living with HIV. These results have implications for nursing, healthcare practice, and policies on infant feeding practices for mothers living with HIV.